Step-by-Step Esthetic Rehabilitation with Chairside System - Rim Kallala; Mohamed Habib Chaouch; Karim Nasr; Teva Courset (Hindawi Limited, 2021)
In modern dentistry, Computer-Aided Design and Manufacturing (CAD/CAM) is a promising technology that allows fabrication of prosthetic restorations through milling procedures. Over years, with the continuous improvement of technology, direct CAD/CAM or "chairside" technology is becoming a widespread approach which offers immediate rehabilitation with long-term rates reported by several studies compared to conventional techniques. All steps are generally carried out in the dental office during the same treatment session. The present paper is about a healthy female patient with a decayed 36 tooth which was restored by ceramic onlay using Planmeca's PlanCAD system. Through the present clinical case, a detailed protocol of chairside technology would be presented from the digital impression to the milling process. It would detail impression steps. It would also highlight especially the virtual design confection of prosthetic restoration using a biogeneric model included in the software. It also illustrated tools which could be used by the dentist to perform the design. Also, some useful tips would be presented in order to perform the confection. On this subject, various studies showed the viability of such technology. To summarize, referring to previous studies, this promising technology allows especially time-saving and patient's comfort compared to the indirect one.